Flexible substrate after etching
The post-etched flexible substrate achieves reduced transmission losses in high-frequency communications by employing a copper conductor layer with alternately stacked current density layers and controlled etching, addressing the challenge of surface roughness and crystal grain size.
Patent Information
- Application Number
- JP2020024879
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-02-18
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2040-02-18
AI Technical Summary
Existing flexible substrates with wiring formed by etching face challenges in achieving a predetermined surface roughness on the sides of the wiring without strict control of etching conditions, particularly when dealing with copper conductor layers having large grains.
A post-etched flexible substrate is developed with a copper conductor layer formed by alternately stacking low and high current density layers, etched using a ferric chloride solution at specific conditions to achieve a surface roughness of 1.0 μm or less on the sides of the wiring.
This approach allows for the reduction of transmission losses in high-frequency radio communications by controlling the surface roughness of the wiring without stringent etching condition controls, while also preventing the increase of crystal grains in the copper conductor layer.
Smart Images

Figure 0007659223000004 
Figure 0007659223000005 
Figure 0007659223000006
Abstract
Description
[Technical field]
[0001] The present invention relates to an etched flexible substrate, and more particularly to an etched flexible substrate on which wiring is formed by etching. [Background technology]
[0002] The amount of data being transmitted and received in portable electronic devices such as smartphones, mobile phones, and tablet computers is increasing. To accommodate this amount of data being transmitted and received, the communication speed of these portable electronic devices is required to be faster, that is, to be wireless at higher frequencies. Therefore, the electronic components used in these portable electronic devices are required to have lower transmission loss when wireless communication at higher frequencies is performed.
[0003] In portable electronic terminals, there is a high need to place components in a small space, and so FPCs (Flexible Printed Circuits) based on a resin film are used. In many FPCs, a polyimide film is used as the base film. As described in Patent Document 1, in FPCs using this polyimide film, a manufacturing method has often been adopted in which a base metal layer is formed by dry plating on the base film, and then a metal layer is formed by wet plating. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2010-205799 A Summary of the Invention [Problem to be solved by the invention]
[0005] Since high frequency signals flow near the surface of the wiring of the FPC, it is preferable that the surface roughness of the wiring is as small as possible. It is relatively easy to make the upper surface of the wiring have a predetermined surface roughness by wet plating conditions. In contrast, the side surface of the wiring is revealed by etching, and there is a problem that the etching conditions must be strictly controlled in order to make the surface roughness a predetermined value. This is particularly noticeable when the crystal grains of the copper conductor layer are large when wet plating is performed. For example, since the size of the crystal grains changes over time after wet plating, in order to ensure a predetermined surface roughness, it may be necessary to select etching conditions that match the size of the crystal grains after wet plating.
[0006] In view of the above circumstances, the present invention aims to provide an etched flexible substrate in which the surface roughness of the side surface of the wiring after etching under predetermined conditions is a predetermined value without the need for strict control of the etching conditions, thereby reducing transmission loss in high-frequency wireless communication. [Means for solving the problem]
[0007] The post-etching flexible substrate of the first invention is a post-etching flexible substrate obtained by etching a flexible substrate having a base film, a base metal layer directly superimposed on the base film, and a copper conductor layer directly superimposed on the base metal layer, and the copper conductor layer has a current density of 0.2 A / dm 2 More than 0.4A / dm 2 A low current density layer formed at a current density of less than 0.4 A / dm 2 and a high current density layer formed at a current density of 1.0 μm or more. When etched for 70 seconds with an etching solution of ferric chloride solution with a concentration of 15 wt % at a shower pressure of 0.3 MPa, the surface roughness Rz of the side surface of the wiring is 1.0 μm or less. The high current density layer is sandwiched between two of the low current density layers, and the thickness between the two low current density layers is 1.00 μm or less. It is characterized by: No. 2 The etched flexible substrate of the invention is the first Clearly The base film is a high frequency compatible base film. No. 3 The etched flexible substrate of the invention is the first invention Or the second invention In the present invention, the base metal layer is composed of a nickel-chromium alloy layer directly superimposed on the base film and a base copper layer directly superimposed on the nickel-chromium alloy layer, and the thickness of the nickel-chromium alloy layer is 2 nm or more and 50 nm or less. Effect of the Invention
[0008] According to the first invention, when etching is performed for 70 seconds with an etching solution of ferric chloride solution with a concentration of 15 wt % at a shower pressure of 0.3 MPa, the surface roughness Rz of the side surface of the wiring is 1.0 μm or less, and the surface roughness of the peripheral surface including the upper surface and flat surface of the wiring is also small, so that a post-etching flexible substrate with reduced transmission loss in high-frequency wireless communication can be provided. In other words, even if the etching conditions are not strictly controlled, a post-etching flexible substrate with reduced transmission loss in high-frequency wireless communication can be provided. In addition, since the copper conductor layer is formed by stacking a low current density layer having a current density less than a predetermined current density and a high current density layer having a current density equal to or greater than the predetermined current density, the crystal grains in the copper conductor layer can be prevented from becoming large by the simple method of adjusting the current density for forming the copper conductor layer. Also, By setting the thickness between the two low current density layers to 1.00 μm or less, the size of the crystals during recrystallization can be more reliably suppressed. No. 2 According to the invention, since the base film is a high frequency compatible base film, the transmission loss in high frequency wireless communication can be made smaller than in the case where polyimide is used as the base film. No. 3 According to the invention, the thickness of the nickel-chromium alloy layer constituting the base metal layer is 2 nm or more and 50 nm or less, so that the nickel-chromium alloy layer, which has a large transmission loss, is thin, and therefore a post-etching flexible substrate suitable for higher frequency wireless communication can be provided. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is an explanatory perspective view of a post-etching flexible substrate according to the first embodiment of the present invention. [Diagram 2] 2 is a cross-sectional view of a flexible substrate prior to the post-etching flexible substrate of FIG. 1. [Diagram 3] FIG. 1 is a cross-sectional view of wiring on an FPC to explain the skin effect. [Figure 4] 3 is a perspective view of a plating apparatus used in the manufacture of the flexible substrate of FIG. 2. [Diagram 5] FIG. 5 is a plan view of a plating tank constituting the plating apparatus of FIG. [Figure 6] FIG. 2 is an SEM image of the flexible substrate after etching according to the first embodiment. [Figure 7] FIG. 13 is an SEM image of a post-etching flexible substrate according to the second embodiment. [Figure 8] FIG. 13 is an SEM image of a flexible substrate after etching in a comparative example. [Figure 9] 1 is a graph showing the relationship between frequency and transmission loss. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Next, an embodiment of the present invention will be described with reference to the drawings. First, the pre-etching flexible substrate 10a will be described, and then the post-etching flexible substrate 10 will be described. However, the embodiment shown below is an example of the post-etching flexible substrate 10 for embodying the technical concept of the present invention, and the post-etching flexible substrate 10 of the present invention is not limited to the one described below. Note that the size or positional relationship of the members shown in each drawing may be exaggerated for clarity of explanation.
[0011] (Flexible substrate 10a) FIG. 2 shows a cross-sectional view of a flexible substrate 10a corresponding to a previous stage of the post-etching flexible substrate 10 according to the first embodiment of the present invention. As shown in FIG. 2, the flexible substrate 10a includes a base film 11, a base metal layer 12 formed on one side of the base film 11, and a copper conductor layer 20 formed so as to overlap the base metal layer 12. The base metal layer 12 is formed, for example, by laminating a nickel-chromium alloy layer 13 and a base copper layer 14 provided on the base film 11 side. Note that FIG. 2 shows a flexible substrate 10a having the base metal layer 12 and the like formed on one side of the base film 11, but the post-etching flexible substrate 10 of the present invention also includes a flexible substrate 10a having the base metal layer 12 and the like formed on both sides of the base film 11, which is etched.
[0012] (Base film 11) The base film 11 used in the flexible substrate 10a is a resin film, for example, a polyimide film. Furthermore, a high-frequency compatible base film having good dielectric properties is preferable compared to a polyimide film. For example, LCP (Liquid Crystal Plymer) or PEEK (Poly Ether Ether Ketone) corresponds to the high-frequency compatible base film. These films have good dielectric properties and do not cause large transmission loss even when used for high-frequency wireless communication. Other possible high-frequency compatible base films include PET (Polyethylene Terephthalate), PEN (Polyethylene Naphthalate), PTFE (Polytetrafluoroethylene), COP (Cyclo Olefin Polymers), SPS (Syndiotactic Polystyrene), and COC (Cyclic Olefin Copolymer).
[0013] (Base metal layer 12) The flexible substrate 10a has an underlying metal layer 12 for increasing the adhesive strength between the copper conductor layer 20 and the base film 11. The underlying metal layer 12 is directly superimposed on the base film 11. The underlying metal layer 12 preferably includes a nickel-chromium alloy layer 13 directly superimposed on the base film 11, and an underlying copper layer 14 directly superimposed on the nickel-chromium alloy layer 13. The nickel-chromium alloy layer 13 may be a nickel layer made only of nickel, or a chromium layer made only of chromium.
[0014] The nickel-chromium alloy layer 13 is preferably formed by sputtering, which is a dry plating method, but may also be formed by other dry plating methods such as vacuum deposition and ion plating.
[0015] The thickness of the nickel-chromium alloy layer 13 is preferably 2 nm or more and 50 nm or less. Furthermore, the thickness of the nickel-chromium alloy layer 13 is more preferably 2 nm or more and 4 nm or less. If the thickness of the nickel-chromium alloy layer 13 is less than 2 nm, adhesion problems are likely to occur during each subsequent processing step. If it is thicker than 50 nm, it becomes difficult to remove nickel or chromium during wiring processing, and cracks or warping are likely to occur in the nickel-chromium alloy layer 13, which makes it more likely to cause adhesion problems between the base film 11 and the underlying metal layer 12. In addition, if the thickness of the nickel-chromium alloy layer 13 is greater than 50 nm, it will affect high-frequency communication. In order to reduce this effect, the thickness of the nickel-chromium alloy layer 13 is more preferably 4 nm or less.
[0016] When high-frequency communication is performed, the skin effect causes the current passing through the wiring to flow closer to the skin. Fig. 3 shows a cross-sectional view of wiring on an FPC to explain the skin effect. That is, Fig. 3 is a cross-sectional view of one of the wirings present on a post-etching flexible substrate 10 after etching or the like is performed on a flexible substrate 10a. A base metal layer 12 made of a nickel-chromium alloy layer 13 and a base copper layer 14 is provided on a base film 11, and a copper conductor layer 20 is provided so as to overlap the base metal layer 12.
[0017] For example, when the skin effect occurs, the current flows easily in the skin part (the part shown by dots in FIG. 3) and does not flow easily inside. In reality, the skin effect appears in stages, but in FIG. 3, the skin part is shown separately from the other parts for easy understanding. Here, the skin part includes the nickel-chromium alloy layer 13, and considering the electrical resistance, the resistance of the nickel-chromium alloy layer 13 is higher than the copper conductor layer 20 and the like, and the current does not flow easily. However, in high-frequency communication, since the current flowing in the skin part is large, it is presumed that the absence of the nickel-chromium alloy layer 13 with high resistance or making it as thin as possible leads to a reduction in the resistance of the entire wiring. For this reason, the thickness of the nickel-chromium alloy layer 13 is more preferably 4 nm or less.
[0018] The weight percentage of chromium in the nickel-chromium alloy layer 13 is preferably greater than or equal to 12 percent and less than or equal to 50 percent.
[0019] The copper underlayer 14 is formed by a dry plating method so as to overlap the nickel-chromium alloy layer 13. The copper underlayer 14 is preferably formed by sputtering, which is a dry plating method. However, the copper underlayer 14 may also be formed by other dry plating methods such as vacuum deposition and ion plating.
[0020] The thickness of the underlying copper layer 14 is preferably 50 nm or more and 500 nm or less. If the thickness of the underlying copper layer 14 is less than 50 nm, the effect of reducing defects due to pinholes is reduced and there is a possibility of causing poor electrical conductivity during the subsequent wet plating. If the thickness exceeds 500 nm, the underlying copper layer 14 is prone to cracking or warping, which may cause problems with the adhesion between the base film 11 and the underlying metal layer 12.
[0021] (Copper conductor layer 20) The flexible substrate 10a has a copper conductor layer 20 directly superimposed on the base metal layer 12. The copper conductor layer 20 is formed directly on the surface of the base metal layer 12 by electrolytic plating. When the flexible substrate 10a is to be a flexible wiring substrate by a semi-additive method, the thickness of the copper conductor layer 20 is generally 0.1 to 5 μm. This is because the flexible substrate 10a has good handleability. When the flexible substrate 10a is to be a flexible wiring substrate by a subtractive method, the thickness of the copper conductor layer 20 is generally 8 to 12 μm. However, the thickness of the flexible substrate 10a is not limited to these values.
[0022] In order to make the surface roughness Rz of the side of the wiring of the etched flexible substrate 10 1.0 μm or less after etching the flexible substrate 10a under predetermined conditions, it is necessary that the crystal grains in the copper conductor layer 20 do not become larger than a predetermined size. The simplest method for suppressing the crystal grains of the copper conductor layer 20 from becoming larger is when the copper conductor layer 20 is formed by alternately overlapping low current density layers 21 and high current density layers 22 as shown in FIG. 2. The thickness of the high current density layer 22 is preferably 0.20 μm or more and 1.00 μm or less, as described later. Other methods for suppressing the crystal grains from becoming larger include a method of providing multiple plating tanks that store plating solutions with different components, and a method of providing multiple plating tanks with different temperatures.
[0023] In Fig. 2, three high current density layers 22 are provided in the copper conductor layer 20, sandwiching two low current density layers 21 in order. That is, the high current density layer 22 is first provided so as to directly overlap the base metal layer 12. Next, the low current density layer 21 is provided so as to directly overlap this. Next, the high current density layer 22 is provided so as to directly overlap this. Next, the low current density layer 21 is provided so as to directly overlap this. And finally, the high current density layer 22 is provided again. This high current density layer 22, which is located at the top in the plane of Fig. 2, becomes the surface of the flexible substrate 10a.
[0024] Productivity can be maintained by directly overlapping the high current density layer 22 on the base metal layer 12. In addition, the high current density layer 22 is provided on the outermost side of the copper conductor layer 20, improving the gloss of the outermost surface of the flexible substrate 10a.
[0025] There is no limitation on the number of low current density layers 21 or high current density layers 22. In addition, it is preferable that the low current density layers 21 and the high current density layers 22 are alternately laminated.
[0026] The low current density layer 21 is a layer that is electrolytically plated at a current density lower than the current density when the high current density layer 22 is electrolytically plated, and refers to a layer that is plated under the same conditions of current density, plating temperature, and plating solution composition when the part is plated within a predetermined range in the thickness direction. The "predetermined range" here can be determined arbitrarily by the manufacturer of the flexible substrate 10a. For example, the predetermined range can be 0.1 μm. The current density, plating temperature, and plating solution composition do not need to be constant.
[0027] For example, the current density in the low current density layer 21 of the flexible substrate 10a is 0.2 A / dm 2 More than 0.4A / dm 2 The current density in the high current density layer 22 is less than 0.4 A / dm 2 More than 10A / dm 2It can be as follows:
[0028] Since the copper conductor layer 20 is formed by stacking a low current density layer 21 having a current density less than a predetermined current density and a high current density layer 22 having a current density equal to or greater than a predetermined current density, the crystal grains of the copper conductor layer 20 can be prevented from becoming large by the simple method of adjusting the equipment for forming the copper conductor layer 20.
[0029] The thickness of each of the high current density layers 22 constituting the copper conductor layer 20 is preferably 0.20 μm or more and 1.00 μm or less. In the above, there is only one high current density layer 22 between the low current density layers 21, but in the case of two or more layers, the value between the two low current density layers 21 is preferably 0.20 μm or more and 1.00 μm or less. When the current density varies from layer to layer, this thickness can be controlled by the time per electrolytic plating for forming the layer. When electrolytic plating is performed while transporting the substrate 10b by roll-to-roll, the length of each high current density zone HZ is set so that the plating time is such that a layer having a thickness of 0.20 μm or more and 1.00 μm or less is formed in relation to the transport speed of the substrate 10b.
[0030] Here, the thickness of each layer of the copper conductor layer 20 is calculated from the current density and plating time in electrolytic plating. Specifically, as shown in equation (1), the current density J [A / dm 2 ], plating time T [min], and a given coefficient k are multiplied to obtain thickness d [μm]. Note that coefficient k is a value that depends on conditions such as the plating solution, and is determined by testing.
[0031] [Number 1] d = k × J × T (1)
[0032] The copper conductor layer 20 having such a structure has the property that the recrystallization proceeds slowly. Although the reason is not entirely clear, it is generally believed to be as follows. The copper conductor layer 20 has a structure in which a layer (low current density layer 21) having a high concentration of impurities derived from additives in the copper plating solution and a layer (high current density layer 22) having a low concentration are alternately laminated. The recrystallization proceeds slowly in the copper conductor layer 20 because the impurities in the copper conductor layer 20 inhibit the recrystallization. When the thickness between the two low current density layers 21 is 0.20 to 1.00 μm, the effect of slowing down the recrystallization proceeding in the copper conductor layer 20 is high.
[0033] By setting the thickness between the two low current density layers 21 to 1.00 μm or less, the size of the crystals during recrystallization can be more reliably suppressed.
[0034] (Description of an example of a method for forming the copper conductor layer 20) A method for forming the copper conductor layer 20 by changing the current density during electrolytic plating will be described below with reference to FIGS.
[0035] Fig. 4 shows a perspective view of a plating apparatus 3 used in manufacturing the flexible substrate 10a, and Fig. 5 shows a plan view of a plating tank 40 constituting the plating apparatus 3 of Fig. 4. The plating apparatus 3 is an apparatus that performs electrolytic plating on a long strip-shaped substrate 10b while transporting the substrate 10b by a roll-to-roll method. The plating apparatus 3 has a supply device 31 that pays out the substrate 10b wound in a roll, and a winding device 32 that winds up the substrate 10b (flexible substrate 10a) after plating in a roll.
[0036] The plating apparatus 3 also has a pair of upper and lower endless belts 33 (the lower endless belt 33 is not shown) that transport the substrate 10b. Each endless belt 33 is provided with a plurality of clamps 34 that grip the substrate 10b. The substrate 10b fed from the supply device 31 is suspended with its width direction aligned vertically, and both edges are gripped by the upper and lower clamps 34. The substrate 10b is rotated within the plating apparatus 3 by the drive of the endless belts 33, and then released from the clamps 34 and taken up by the take-up device 32.
[0037] A pre-treatment tank 35, a plating tank 40, and a post-treatment tank 36 are arranged on the transport path of the substrate 10b. While the substrate 10b is transported through the plating tank 40, a copper conductor layer 20 is formed on the surface of the substrate 10b by electrolytic plating. In this way, a long strip-shaped flexible substrate 10a is obtained.
[0038] As shown in Fig. 4, the plating tank 40 is a single tank that is long horizontally along the transport direction of the substrate 10b. The substrate 10b is transported along the center of the plating tank 40. A copper plating solution is stored in the plating tank 40. The substrate 10b transported in the plating tank 40 is entirely immersed in the copper plating solution.
[0039] The copper plating solution contains a water-soluble copper salt. Any water-soluble copper salt that is generally used in copper plating solutions may be used without any particular limitation. Examples of the water-soluble copper salt include inorganic copper salts, copper salts of alkanesulfonic acids, copper salts of alkanolsulfonic acids, and copper salts of organic acids. Examples of the inorganic copper salt include copper sulfate, copper oxide, copper chloride, and copper carbonate. Examples of the copper salts of alkanesulfonic acids include copper methanesulfonate and copper propanesulfonate. Examples of the copper salts of alkanolsulfonic acids include copper isethionate and copper propanolsulfonate. Examples of the copper salts of organic acids include copper acetate, copper citrate, and copper tartrate.
[0040] As the water-soluble copper salt used in the copper plating solution, one type selected from inorganic copper salts, copper salts of alkanesulfonic acids, copper salts of alkanolsulfonic acids, copper salts of organic acids, etc. may be used alone, or two or more types may be used in combination. For example, as in the case of combining copper sulfate and copper chloride, two or more different types within one category selected from inorganic copper salts, copper salts of alkanesulfonic acids, copper salts of alkanolsulfonic acids, copper salts of organic acids, etc. may be used in combination. However, from the viewpoint of management of the copper plating solution, it is preferable to use one type of water-soluble copper salt alone.
[0041] The copper plating solution may contain sulfuric acid. By adjusting the amount of sulfuric acid added, the pH and sulfate ion concentration of the copper plating solution can be adjusted.
[0042] The copper plating solution contains additives that are generally added to plating solutions. Examples of the additives include a leveler component, a polymer component, a brightener component, and a chlorine component. As the additive, one selected from the leveler component, polymer component, brightener component, and chlorine component may be used alone, or two or more may be used in combination.
[0043] The leveler component is composed of an amine containing nitrogen. As the leveler component, although it is not particularly limited, it is preferable to use one type selected from diallyldimethylammonium chloride, Janus Green B, etc., alone or in combination of two or more types. As the polymer component, although it is not particularly limited, it is preferable to use one type selected from polyethylene glycol, polypropylene glycol, and polyethylene glycol-polypropylene glycol copolymer, alone or in combination of two or more types. As the brightener component, although it is not particularly limited, it is preferable to use one type selected from bis(3-sulfopropyl) disulfide (abbreviated as SPS), 3-mercaptopropane-1-sulfonic acid (abbreviated as MPS), etc., alone or in combination of two or more types. As the chlorine component, although it is not particularly limited, it is preferable to use one type selected from hydrochloric acid, sodium chloride, etc., alone or in combination of two or more types.
[0044] The content of each component of the copper plating solution can be selected arbitrarily. However, the copper plating solution preferably contains 15 to 70 g / L of copper and 20 to 250 g / L of sulfuric acid. In this way, the copper conductor layer 20 can be formed at a sufficient speed. The copper plating solution preferably contains 1 to 50 mg / L of a brightener component. In this way, the precipitated crystals can be made fine and the surface of the copper conductor layer 20 can be made smooth. The copper plating solution preferably contains 1 to 300 mg / L of a leveller component. In this way, protrusions can be suppressed and a flat copper conductor layer 20 can be formed. The copper plating solution preferably contains 10 to 1500 mg / L of a polymer component. In this way, current concentration at the end of the substrate 10b can be alleviated and a uniform copper conductor layer 20 can be formed. The copper plating solution preferably contains 20 to 80 mg / L of a chlorine component. In this way, abnormal deposition can be suppressed.
[0045] The temperature of the copper plating solution is preferably 20 to 35° C. In addition, it is preferable to stir the copper plating solution in the plating tank 40. The means for stirring the copper plating solution is not particularly limited, but a means using a jet flow can be used. For example, the copper plating solution can be stirred by spraying the copper plating solution jetted from a nozzle onto the substrate 10b.
[0046] 5, a plurality of anodes 41 are arranged in the plating tank 40 along the transport direction of the substrate 10b. The clamps 34 that hold the substrate 10b also function as cathodes. By passing a current between the anodes 41 and the clamps 34 (cathode), the copper conductor layer 20 can be formed on the surface of the substrate 10b.
[0047] In the plating tank 40 shown in FIG. 5, anodes 41 are disposed on both the front and back sides of the base material 10b, but in the case of the flexible substrate 10a shown in FIG. 2, electricity is applied to only one side of the base material 10b.
[0048] A rectifier is connected to each of the multiple anodes 41 arranged inside the plating tank 40. Therefore, it is possible to set a different current density for each anode 41. In the flexible substrate 10a shown in Fig. 2, the inside of the plating tank 40 is divided into multiple zones along the transport direction of the base material 10b. Each zone corresponds to an area where one or more continuous anodes 41 are arranged.
[0049] Each zone is configured as a low current density zone LZ or a high current density zone HZ. In the low current density zone LZ, the current density is set to zero or a relatively low "low current density", and electrolytic plating is performed on the substrate 10b at a low current density. In the high current density zone HZ, the current density is set to a "high current density" higher than the low current density, and electrolytic plating is performed on the substrate 10b at a high current density.
[0050] As described above, the current density in the low current density zone LZ (low current density) is set to 0.2 A / dm 2 More than 0.4A / dm 2 It is preferable to set the current density (high current density) in the high current density zone HZ to less than 0.4 A / dm 2 More than 10A / dm 2 It is preferable to set the following:
[0051] The copper conductor layer 20 directly superimposed on the base metal layer 12 is preferably a high current density layer 22. When the copper conductor layer 20 is divided into a high current density layer 22 and a low current density layer 21 by changing the current density, the current density must be high enough to maintain a predetermined productivity, and at the same time low enough not to cause plating burn. This current density is a current density that can generate the high current density layer 22, and is preferably a relatively low current density among the current densities that can generate the high current density layer 22. Specifically, the current density is 0.4 A / dm 2 More than 0.5A / dm 2 It is preferable to set the following:
[0052] It is preferable that the low current density zones LZ and the high current density zones HZ are alternately provided along the transport direction of the substrate 10b. The number of low current density zones LZ may be one or more. The number of high current density zones HZ may be one or more. Based on the transport direction of the substrate 10b, the most upstream zone may be the low current density zone LZ or the high current density zone HZ. Also, the most downstream zone may be the low current density zone LZ or the high current density zone HZ. It is preferable that the most downstream zone is the high current density zone HZ.
[0053] When multiple low current density zones LZ are arranged in the plating tank 40, the current densities in the multiple low current density zones LZ may be the same or different. When multiple high current density zones HZ are arranged in the plating tank 40, the current densities in the multiple high current density zones HZ may be the same or different. However, it is preferable that the current density in the high current density zone HZ is set to increase stepwise toward the downstream side in the transport direction of the substrate 10b.
[0054] The low current density zone LZ and the high current density zone HZ can be provided alternately over the entire region of the plating tank 40 along the transport direction of the substrate 10b. The low current density zone LZ and the high current density zone HZ can also be provided alternately in a part of the downstream region of the plating tank 40 along the transport direction of the substrate 10b. In this case, in the upstream region, electrolytic plating may be performed under conditions different from those of the low current density zone LZ and the high current density zone HZ. If the current density is too high at the beginning of electrolytic plating, the part of the substrate 10b that is in contact with the power supply part (clamp 34) may dissolve. In order to prevent this and increase productivity, the current density is increased stepwise. In the upstream region of the plating tank 40, the current density may be increased stepwise.
[0055] The substrate 10b is electroplated while passing alternately through a low current density zone LZ and a high current density zone HZ. That is, in the plating tank 40, electroplating at a low current density and electroplating at a high current density are alternately and repeatedly performed on the substrate 10b. As a result, the copper conductor layer 20 is formed.
[0056] (Explanation of Etching Method of Flexible Substrate 10a) Flexible substrate 10a is subjected to wiring processing by the following etching to produce post-etching flexible substrate 10. Fig. 1 shows an explanatory perspective view of post-etching flexible substrate 10 according to the first embodiment of the present invention.
[0057] A dry film resist is applied to the surface of the copper conductor layer 20 of the flexible substrate 10a, and then exposed and developed, to obtain a resist having a wiring shape on the flexible substrate 10a. The resist used here is, for example, NIT500 manufactured by Nikko Materials Co., Ltd., and has a thickness of 10 μm. Next, a ferric chloride solution at 40° C. is sprayed onto the flexible substrate 10a in this state, dissolving the copper conductor layer 20 and the underlying metal layer 12 in the portion not covered with the resist. A ferric chloride solution having a concentration of 15 wt % is sprayed onto the flexible substrate 10a at a shower pressure of 0.3 MPa for a time period corresponding to the combined thickness of the copper conductor layer 20 and the underlying metal layer 12, for example, 70 seconds, using an etching solution with a predetermined concentration, thereby dissolving a portion of the copper conductor layer 20 and the underlying metal layer 12. An example of the shower nozzle used here is a uniform spray type spray nozzle, and in this case, the shower pressure of 0.3 MPa is the pressure at the spray nozzle. In addition, the distance from the spray nozzle to the flexible substrate 10a is preferably, for example, 15 cm. These conditions are preferably used when the thickness of the copper conductor layer 20 is 8.0 μm, for example. The resist of the flexible substrate 10a in this state is stripped off with sodium hydroxide at 70° C. The flexible substrate 10 after the resist has been stripped off is the post-etching flexible substrate 10 according to this embodiment. Note that the etching liquid may be not only a ferric chloride liquid with a concentration of 15 wt %, but also a cupric chloride liquid with a concentration of 2 wt %. EXAMPLES
[0058] Specific examples of the copper-clad laminate 1 according to the present invention will be described below, but the present invention is not limited to these examples.
[0059] Example 1 <Flexible substrate 10a> A polyimide film (Upilex-35SGAV1 manufactured by Ube Industries) having a thickness of 35 μm was used as the base film 11. A base metal layer 12 was formed on this base film 11 by a magnetron sputtering device. A nickel-chromium alloy target and a copper target were placed in the magnetron sputtering device. The composition of the nickel-chromium alloy target was 20 mass % Cr and 80 mass % Ni. In a vacuum atmosphere, a nickel-chromium alloy layer 13 made of a nickel-chromium alloy having a thickness of 25 nm and a base copper layer 14 having a thickness of 150 nm were formed thereon on one side of the base film 11.
[0060] The copper plating solution used to form the copper conductor layer 20 is as follows. The copper plating solution contained 120 g / L of copper sulfate, 70 g / L of sulfuric acid, 16 mg / L of a brightener component, 20 mg / L of a leveler component, 1,100 mg / L of a polymer component, and 50 mg / L of a chlorine component. Bis(3-sulfopropyl) disulfide (a reagent manufactured by RASCHIG GmbH) was used as the brightener component. Diallyldimethylammonium chloride-sulfur dioxide copolymer (PAS-A-5 manufactured by Nittobo Medical Co., Ltd.) was used as the leveler component. Polyethylene glycol-polypropylene glycol copolymer (UNILUBE 50MB-11 manufactured by NOF Corporation) was used as the polymer component. Hydrochloric acid (35% hydrochloric acid manufactured by Wako Pure Chemical Industries, Ltd.) was used as the chlorine component.
[0061] The substrate 10b on which the underlying copper layer 14 had been formed was supplied to the plating tank 40 in which the copper plating solution was stored. A copper conductor layer 20 was formed on one side of the substrate 10b by electrolytic plating. The temperature of the copper plating solution at this time was 31° C. During the electrolytic plating, the copper plating solution was agitated by spraying the copper plating solution from a nozzle substantially perpendicularly to the surface of the substrate 10b.
[0062] In Example 1, as shown in Table 1, copper conductor layer 20 was formed by laminating low current density layer 21 and high current density layer 22 so that the surface roughness Rz on the side surface of the wiring after etching would be 1.0 μm or less. In Table 1, the layer numbers are numbered in order from the layer in contact with the surface of base metal layer 12. The current density of even-numbered layers among the 8th to 23rd layers, which are omitted in the middle, is 0.3 A / dm 2 The plating time is 52 seconds, the same as for the sixth layer. The current density for the odd-numbered layers is a high current density of 6.0 A / dm 2 and the plating time was 26 seconds, the same as for the seventh layer. As a result, the low current density layers 21 from the fourth layer to the twenty-sixth layer had a layer thickness of 0.06 μm, and the high current density layers 22 from the fifth layer to the twenty-seventh layer had a layer thickness of 0.57 μm. The first to third layers are high current density layers 22 for stepping up to the high current density layers 22 from the fourth layer onwards. Through the above process, a copper conductor layer 20 of 7.9 μm was obtained.
[0063] [Table 1]
[0064] <Flexible substrate 10 after etching> A 10 μm-thick dry film resist NIT500 was applied to the flexible substrate 10a, exposed, and developed. Then, a ferric chloride solution with a concentration of 15 wt % and a temperature of 40° C. was sprayed onto the flexible substrate 10a in this state for 70 seconds at a shower pressure of 0.3 MPa. This resulted in the flexible substrate 10 after etching.
[0065] FIG. 6 shows the result of observing the state of the side of the wiring in the etched flexible substrate 10 by SEM. The surface roughness of the end face of the wiring in the etched flexible substrate 10 was measured by a Keyence laser microscope VK-9510. As a result of measuring the line roughness of 100 μm three times in the longitudinal direction of the wiring end face at 3000 times magnification, the average value of Rz was 0.46 μm. In addition, FIG. 9 shows a graph of the relationship between frequency and transmission loss in the etched flexible substrate 10 of Example 1. This relationship between frequency and transmission loss was measured by a microwave network analyzer E8363C manufactured by Keysight. The transmission loss varies depending on the surface roughness of the top surface of the wiring, the thickness of the nickel-chromium alloy layer 13, the type of base film 11, etc., but for the configuration of Example 1, if the transmission loss at a frequency of 10 GHz is higher than -8 dB / 200 mm, it was considered to be acceptable. In Example 1, the transmission loss at a frequency of 10 GHz was -4.8 dB / 200 mm, which was acceptable.
[0066] Example 2 <Flexible substrate 10a> A flexible substrate 10a was manufactured in the same manner as in Example 1, except that the method of forming the copper conductor layer 20 by electrolytic plating was as shown in Table 2.
[0067] In Example 2, as shown in Table 2, copper conductor layer 20 was formed by laminating low current density layer 21 and high current density layer 22 so that the surface roughness Rz of the side surface of the wiring after etching would be 1.0 μm or less. In Table 2, the layer numbers are numbered in order from the layer in contact with the surface of base metal layer 12. The current density of even-numbered layers among the 8th to 13th layers, which are omitted in the middle, is 0.3 A / dm 2 The plating time is 52 seconds, the same as for the sixth layer. The current density for the odd-numbered layers is a high current density of 6.0 A / dm 2The plating time was 45 seconds, the same as for the seventh layer. As a result, the low current density layers 21 from the fourth layer to the sixteenth layer had a layer thickness of 0.06 μm, and the high current density layers 22 from the fifth layer to the seventeenth layer had a layer thickness of 0.99 μm. The first to third layers are high current density layers 22 for stepping up to the high current density layers 22 from the fourth layer onwards. Through the above process, a copper conductor layer 20 of 7.7 μm was obtained.
[0068] [Table 2]
[0069] <Flexible substrate 10 after etching> A 10 μm-thick dry film resist NIT500 was applied to the flexible substrate 10a, exposed, and developed. Then, a ferric chloride solution with a concentration of 15 wt % and a temperature of 40° C. was sprayed onto the flexible substrate 10a in this state for 70 seconds at a shower pressure of 0.3 MPa. This resulted in the flexible substrate 10 after etching.
[0070] FIG. 7 shows the result of observing the state of the side of the wiring in the etched flexible substrate 10 by SEM. The measurement method was the same as in Example 1. As a result of the measurement, Rz was 0.78 μm. In addition, FIG. 9 shows a graph measuring the relationship between frequency and transmission loss in the etched flexible substrate 10 of Example 2. This relationship between frequency and transmission loss was measured using the same measuring device as in Example 1. In Example 2, the transmission loss at a frequency of 10 GHz was -7.2 dB / 200 mm, which was acceptable.
[0071] Comparative Example 1 <Flexible substrate 10a> A flexible substrate 10a was manufactured in the same manner as in Example 1, except that the method of forming the copper conductor layer 20 by electrolytic plating was as shown in Table 3.
[0072] In Comparative Example 1, the copper conductor layer 20 was formed by laminating four high current density layers 22 with different current densities, as shown in Table 3. In Table 2, the layer numbers are numbered in order from the layer in contact with the surface of the base metal layer 12. The fourth high current density layer 22 had a current density of 6.0 A / dm 2 Electrolytic plating was carried out for 340 seconds at a current density of 1000 .mu.m. The first to third layers are high current density layers 22 for stepping up to the fourth and subsequent high current density layers 22. A copper conductor layer 20 of 7.8 μm was obtained by the above steps.
[0073] [Table 3]
[0074] <Flexible board after etching> A 10 μm-thick dry film resist NIT500 was applied to the flexible substrate 10a, exposed, and developed. Then, a ferric chloride solution with a concentration of 15 wt% and a temperature of 40° C. was sprayed onto the flexible substrate 10a in this state for 70 seconds at a shower pressure of 0.3 MPa. This resulted in an etched flexible substrate.
[0075] FIG. 8 shows the result of observing the state of the side of the wiring in the flexible substrate after etching by SEM. The measurement method was the same as in Example 1. As a result of the measurement, Rz was 1.19 μm. In addition, FIG. 9 shows a graph measuring the relationship between frequency and transmission loss in the flexible substrate after etching in Comparative Example 1. This relationship between frequency and transmission loss was measured using the same measuring device as in Example 1. In Comparative Example 1, the transmission loss at a frequency of 10 GHz was -8.3 dB / 200 mm, which was unacceptable. [Explanation of symbols]
[0076] 10 Flexible substrate after etching 10a Flexible PCB 11 Base film 12 Undercoat metal layer 13 Nickel-chromium alloy layer 14 Undercoat copper layer 20 Copper conductor layer 21 Low current density layer 22 High current density layer
Claims
1. A post-etching flexible substrate obtained by etching a flexible substrate including a base film, a base metal layer directly superimposed on the base film, and a copper conductor layer directly superimposed on the base metal layer, The copper conductor layer is 0.2A / dm 2 0.4A / dm or more 2 a low current density layer formed at a current density of less than 0.4 A / dm 2 and a high current density layer formed at a current density of at least When etching is performed for 70 seconds with an etching solution of ferric chloride solution having a concentration of 15 wt % at a shower pressure of 0.3 MPa, the surface roughness Rz of the side surface of the wiring is 1.0 μm or less, the high current density layer is sandwiched between two of the low current density layers, The thickness between the two low current density layers is 1.00 μm or less; A post-etch flexible substrate.
2. The base film is It is a high frequency compatible base film. The post-etch flexible substrate according to claim 1 .
3. the underlying metal layer includes a nickel-chromium alloy layer directly superimposed on the base film, and an underlying copper layer directly superimposed on the nickel-chromium alloy layer, The thickness of the nickel-chromium alloy layer is 2 nm or more and 50 nm or less.
3. The etched flexible substrate according to claim 1 or 2.
Citation Information
Patent Citations
Wiring board and its manufacturing method
JP2003273509A
Flexible wiring board and its manufacturing method
JP2007189177A
Substrate for flexible wiring board and method for manufacturing the same
JP2009295656A
Two-layer plated substrate and method of manufacturing the same
JP2010205799A
Ceramics circuit board
JP2014207482A